2013
DOI: 10.1097/iae.0b013e31826af556
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Sirt1 in Choroidal Neovascular Membranes

Abstract: SIRT1 levels appear elevated in human choroidal neovascularization membranes compared with control eyes. Moreover, inhibition of SIRT1 activity is correlated with decreased secretion of potent proangiogenic cytokines. Collectively, these data support a potential role for SIRT1 in the pathogenesis of neovascular age-related macular degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 25 publications
1
14
0
1
Order By: Relevance
“…In the present study, SIRT1 expression levels were reduced in the PBMCs of patients with PDR and, following treatment of the PBMCs with a SIRT1 activator, resveratrol, SIRT1 expression levels were upregulated. Consistent with previous studies (18,19), IL-17 expression levels were inhibited by SIRT1 activation in the present study; however, in contrast with the present hypothesis that SIRT1 expression levels may be downregulated in the fibrovascular membranes of patients with PDR, SIRT1 expression was upregulated, which is consistent with the findings of Maloney et al (37). This may be due to a protective feedback mechanism in the retina; however, the precise underlying mechanism remains unclear and requires further study.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, SIRT1 expression levels were reduced in the PBMCs of patients with PDR and, following treatment of the PBMCs with a SIRT1 activator, resveratrol, SIRT1 expression levels were upregulated. Consistent with previous studies (18,19), IL-17 expression levels were inhibited by SIRT1 activation in the present study; however, in contrast with the present hypothesis that SIRT1 expression levels may be downregulated in the fibrovascular membranes of patients with PDR, SIRT1 expression was upregulated, which is consistent with the findings of Maloney et al (37). This may be due to a protective feedback mechanism in the retina; however, the precise underlying mechanism remains unclear and requires further study.…”
Section: Discussionsupporting
confidence: 91%
“…Whilst it appears evident that SIRT1 is crucial for maintaining integrity and function of RPE cells under oxidative stress and chronic inflammation, results about the role of SIRT1 during neovascularization are controversial [45,46]. In fact, a previous study, observing higher SIRT1 expression level in choroidal neovascularization (CNV) membranes than in healthy donor eyes, demonstrated that SIRT1 inhibition with nicotinamide decreased the secretion of proangiogenic factors, such as VEGF-A, platelet-derived growth factor BB and angiogenin in ARPE-19 cells [47]. By contrast, others revealed that treatment with resveratrol, a natural SIRT1 activator, restored VEGF secretion in RPE cells upon oxidative and inflammatory conditions [48].…”
Section: Discussionmentioning
confidence: 99%
“…There are an increasing number of papers assessing the relationship between SIRT1 and AMD in animal and in vitro studies. 17,18,42 rs12778366 located in the promoter region of SIRT1 gene and has been studied in the schizophrenia, type 2 diabetes, systemic lupus erythematosus, glucose tolerance, and longevity patients. 20,25,43,44 Lots of studies showed rs12778366 is a possible functional SNP in SIRT1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…They found SIRT1 levels elevated in human choroidal neovascularization membranes compared with control eyes. 18 …”
Section: Introductionmentioning
confidence: 99%